The Development of Monopoly Game as Media for Science Learning at Elementary School - M.Jaya Adi Putra; Mauliatun Nisa (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to examine the validity of the development of the game of Monopoly on hydrospheric science learning in grade V Elementary School. Research and Development (RD) research is used in this type of research. The Four-D model describes the research and development process, consisting of four stages: defining, designing, developing, and distributing. The study took place in Pekanbaru in the 2020/2021 academic year with four fifth grade private elementary school students. The Four-D model in this development research is only up to the development stage. The purpose of this research is to develop a product and validate by the validator then test individually. We were collecting data using a Likert scale instrument. Physical aspects, usage aspects, image aspects, colour aspects, writing aspects, and functional aspects obtained an average score of 97.78%, categorized as very valid in the assessment carried out by media expert validators. The assessment results carried out by the material expert validator consisted of the content/material aspect, and the learning aspect resulted in an average score of 90%, which indicated both were very valid. The average individual test evaluation results were 97.78%, categorized as very good. Monopoly game media was declared valid for grade V Elementary School science learning based on data analysis by media experts, material experts, and individual trials.